Prognostic factors in patients with intracerebral haematoma. Issue 8 (August 1992) - Franke, C L; van Swieten, J C; Algra, A; van Gijn, J
Abstract : In a prospective study, the prognostic value of clinical characteristics in 157 consecutive patients with spontaneous supratentorial intracerebral haemorrhage were examined by means of multivariate analysis. Two days after the event 37 (24%) patients had died. Factors independently contributing to the prediction of two day mortality were pineal gland displacement on CT of 3 mm or more (p less than 0.001), blood glucose level on admission of 8.0 mmol/l or more (p = 0.01), eye and motor score on the Glasgow Coma Scale of eight out of 10 or less (p = 0.022) and haematoma volume of 40 cm3 or more (p = 0.037). Between the third day and one year after the event another 46 of the 120 two day survivors had died; the independent prognostic indicators for death during that period were: age 70 years or more (p less than 0.001) and severe handicap (Rankin grade five) on the third day (p less than 0.001). Functional independence (Rankin grade two or less) at one year was most common not only with the converse features of age less than 70 years (p less than 0.01) and Rankin grade four or less on the third day (p = 0.002), but also with an eye and motor score on the Glasgow Coma Scale of nine or 10 on the third day (p less than 0.001). The 120 patients with intracerebral haemorrhage who were still alive two days after the event were matched with 120 patients with cerebral infarction, according to age, level of consciousness on the third day after stroke (Glasgow Coma Scale) and handicap (Rankin grade). Survival and handicap after one year did not differ between these two groups. The conclusion drawn is that it is not the cause (intracerebral haemorrhage or cerebral infarction) but the extent of the brain lesion that determines the outcome in patients who survive the first two days.